2022
DOI: 10.4102/jtscm.v16i0.747
|View full text |Cite
|
Sign up to set email alerts
|

Small and medium enterprises’ adoption of 4IR technologies for supply chain resilience during the COVID-19 pandemic

Abstract: The coronavirus disease 2019 (COVID-19) pandemic that began to spread at the beginning of 2020 revealed the vulnerability of many businesses to supply chain disruptions (Mavilia & Pisani 2021;Nasution et al. 2020; United Nations Industrial Development Organisation [UNIDO] 2020). The lockdown measures instituted in many countries disrupted production flows and regional and global supply chains, reduced demand for non-essential goods and services and forced enterprises to suspend or scale down operations (Ratten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…This has already been practiced for many years by SMEs; therefore, it is not a recent concept, but the magnitude has risen (Fitriasari, 2020.). The utilization of technology will undoubtedly influence how crises are handled today and government backing, which has become a must to sustain a company's existence (Zighan et al ., 2022; Munongo and Pooe, 2022). Our research showed that prosocial leadership is one of the key factors in keeping people calm at work and promoting a sense of community at work.…”
Section: Discussionmentioning
confidence: 99%
“…This has already been practiced for many years by SMEs; therefore, it is not a recent concept, but the magnitude has risen (Fitriasari, 2020.). The utilization of technology will undoubtedly influence how crises are handled today and government backing, which has become a must to sustain a company's existence (Zighan et al ., 2022; Munongo and Pooe, 2022). Our research showed that prosocial leadership is one of the key factors in keeping people calm at work and promoting a sense of community at work.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers also note the impact of Fourth Industrial Revolution (4IR) technologies on SMEs' SCR, illustrating a positive link between 4IR adoption and SCR [56]. The adoption of Industry 4.0 significantly impacts SCR, highlighting the importance of information visibility in the SC [57].…”
Section: Sc Resilience and Ict Adoptionmentioning
confidence: 99%
“…Industry 4.0 technologies include artificial intelligence (AI), IoT, e-commerce platforms, Machine Learning (ML) with Big Data, and virtual reality (VR). To manage and address the negative impact of the pandemic, an increase in the use of these technologies by companies was noted [106], contributing to a more resilient SC; ICT tools, through data collection, analysis and dissemination, improve performance, enabling high flexibility with reduced costs and optimal use of available resources [107]. The use of I4.0-related technologies also requires qualified and skilled personnel, so that companies can benefit from their implementation [108].…”
Section: Interrelated Aspectsmentioning
confidence: 99%